Los programas infantiles transmitidos por televisión y su incidencia en el desarrollo socio-afectivo de los niños y niñas de preparatoria, primer grado de educación general básica de la escuela “General Juan Lavalle” de la ciudad de Riobamba. Período lectivo 2013-2014 - Alomía Pánchez, María Elena (2014)
The present thesis refers to the study on "THE INFANTILE PROGRAMS TRANSMITTED FOR TELEVISION AND ITS INCIDENCE IN BASIC EDUCATION FIRST GRADE CHILDREN’S SOCIO – AFECTIVE DEVELOPMENT "GENERAL JUAN LAVALLE" SCHOOL OF RIOBAMBA CITY. PERÍOD 2013 - 2014", It was developed according to the Regulation of Graduation in validity of the Loja National University. The General Objective was: To determine the incidence of the Programs Infantile transmitted by Television in the Children’s Socio – Affective Development “General Juan Lavalle” School. The methods used in this investigation work were: Scientific, Inductive, Deductive, Descriptive. The applied techniques were the Survey, directed to the children’s teachers, to know if the Infantile Programs Transmitted For Television impact or not in the Socio – Affective Development in them, the Questionnaire that was applied to children’s to know their preferences in television programming; the Guide of Observation and Test of Denver that was applied to children’s, to determine and to evaluate the Development Affective Partner. After analyzing the data obtained by the Survey applied the teachers it concludes that 100% consider that the content of the Transmitted Infantile Programs for Television influence in the children’s Socio- Affective Development, with more incidence the family customs and values. After analyzing the result that they watch of Observation Guide it concludes that 79% of those observed has an average of realization of the Very Satisfactory activities, 15% they carried out the activities with a Satisfactory average, while 6% obtained an average of Not very Satisfactory; It can be evidence clearly that bigger problems don't exist with the Development affective Partner, also when applying Test of Denver we can notice that the 93.9% of them have Normal Socio – Affective Development Showing 6.1% has a Consider Affective Development from normal, demonstrating the information revealed by the Guide of Observation and Test of Denver so agrees in the results of the Children’s Socio – Affective Development